HE IMPLEMENTATION OF MOBILE-ASSISTED EXTENSIVE READING IN SENIOR HIGH SCHOOL (IMPLEMENTASI MEMBACA EKSTENSIF BERBASIS PONSEL DI SEKOLAH MENENGAH ATAS) - Muhammad Andriana Gaffar; Vena Fernanda; Hamdan Hidayat (Metalingua: Jurnal Penelitian Bahasa, 2021)
There is a huge concern among educators about students who are less interested in reading. They are more serious about those who feel bored with reading. It will cause them to feel overwhelmed when given a book or text when asked to analyze or summarize what they have read and cause them to be lazy to read caused by the difficulty to carry books anywhere. Many researchers have tried to find out the reasons behind students' boredom in reading. In an academic context, reading is considered the most important language skill. Through reading, students learn new information. "Book is a window to the world." This expression describes the benefits of reading, which is to open, broaden insight and knowledge. This study was aimed at: (1) How is the implementation of mobile-assisted extensive reading in senior high school? And (2) How is the students’ perception toward the implementation of mobile-assisted extensive reading? This research is a descriptive study with a qualitative approach with a case study design. Data collection is carried through observation, documentation, questionnaires, and interviews. The research participants were 13 students of class X social sciences at MA Al-Husna. The result shows that: (1) the result of the implementation of mobile-assisted extensive reading lessons in Senior High School is implementing fun reading activities so that students did not feel bored and reading interest was the main objective. (2) The result of students' perceptions regarding the implementation of mobile-assisted extensive reading lessons in Senior High School showed that students feel happy to do reading using the Extensive Reading technique, and they feel more interested in reading because they are motivated. This research makes it easier for students to do reading anywhere and anytime using (Smartphone).